2005
DOI: 10.1002/uog.1994
|View full text |Cite
|
Sign up to set email alerts
|

The amniotic sheet: a truly benign condition?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 12 publications
2
35
1
1
Order By: Relevance
“…The current literature regarding the outcome of the abnormal appearance of the amniotic membranes is limited to some small case series and case reports due to the low prevalence of this pathology (between 0.14% and 0.75%) [6]. There are few studies that have identified the causes of amniotic sheets and circumvallate placenta [7,8].…”
Section: Abnormal Ultrasound Appearance Of the Amniotic Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature regarding the outcome of the abnormal appearance of the amniotic membranes is limited to some small case series and case reports due to the low prevalence of this pathology (between 0.14% and 0.75%) [6]. There are few studies that have identified the causes of amniotic sheets and circumvallate placenta [7,8].…”
Section: Abnormal Ultrasound Appearance Of the Amniotic Membranesmentioning
confidence: 99%
“…Amniotic sheets were associated with malpresentations, higher primary cesarean section rates, and preterm births [6]. However, amniotic sheets represent a benign condition that is not associated with fetal deformity or adverse fetal outcome [20].…”
Section: Ultrasound Differential Diagnosismentioning
confidence: 99%
“…They suggested that although the incomplete sheets are benign, complete amniotic sheets may be associated with intrauterine death. The authors hypothesized that the small defects on the complete sheets may predispose the mother and fetus to cord prolapse and intrauterine death (6). None of our patients had a complete sheet or poor pregnancy outcome, which suggests that complete sheets are extremely rare.…”
Section: Discussionmentioning
confidence: 74%
“…All amniotic sheets were classified as incomplete sheets, according to the classification outlined by Tan et al (6). Eight patients had solitary amniotic sheets, whereas one patient had two sheets.…”
Section: Resultsmentioning
confidence: 99%
“…D'autres études [63,64] avaient déjà suggéré une corréla-tion entre présence de synéchies intra-utérines pendant la grossesse et un mauvais pronostic foetal. Ces études rétros-pectives retrouvaient par exemple une augmentation de la mortalité [63], une majoration des accouchements prématu-rés, un plus faible poids de naissance, une augmentation de l'admission en soins intensifs et l'augmentation du nombre d'Apgar inférieur à 7 [64].…”
Section: Autres Complications Obstétricalesunclassified